The Cost of Introducing and Implementing Trade Facilitation Measures Interim Report - Moïsé, Evdokia (OECD Trade Policy Papers, 2004)
This report presents preliminary findings from a series of country surveys on the costs of introducing and implementing trade facilitation measures. It was prepared in response to concerns with respect to the cost implications of a future WTO agreement on trade facilitation and will be complemented in the near future by additional data from a wider range of developing and least-developed countries. The report contains observations with respect to the methodology of assessing trade facilitation costs and highlights common cost features in the various country experiences